Union Jack: Labour Leader Jack Munro - Hak, Gordon H. (Gordon Hugh) (Labour / Le Travail, 1991)
The article reviews the book, "Union Jack: Labour Leader Jack Munro," by Jack Munro and Jane O'Hara.
Keywords: BOOKS -- Reviews; Labor leaders; MUNRO, Jack; Nonfiction; O'HARA, Jane; UNION Jack: Labour Leader Jack Munro (Book)